RANCANG BANGUN ALAT PRAKTIK PENGOPERASIAN POMPA SENTRIFUGAL - Khusairi Ilham, Muhammad (STKIP PGRI Situbondo, 2025)
This project aims to design a centrifugal pump practicum simulation tool for students of the Akamigas PEM Refinery Engineering Department. This simulation tool is designed to provide in-depth practical experience of the operation and characteristics of centrifugal pumps, thus supporting theoretical learning with real applications in the laboratory. In its design, the author made a careful selection of pumps based on the specific needs of the laboratory, such as the required flow capacity and head. The selection of the right pump is very important to ensure that this simulation tool is in accordance with educational objectives and is able to reflect realistic operational conditions. To support pump operations, the author chooses the right fittings such as pipes, elbows, and valves. The selection of fittings is based on technical considerations to ensure efficient fluid flow and reduce pressure loss in the system. Each component is carefully selected to ensure compatibility and optimal performance. In addition, supporting systems such as sturdy brackets and base plates are designed to provide stability and safety of the tool during use. The material and design of the brackets and base plates are selected to be able to withstand the loads and vibrations generated during operation, ensuring that the tool remains stable under various conditions. This simulation tool is not only designed to be functional and efficient, but also to have high durability and be safe to use in an educational environment. The author ensures that this tool meets high safety and quality standards, so it can be used for a long time without reducing performance.